The Islamic Perspective on Trilogy Epistemology: Bayāni, Burhāni, and ‘Irfāni - Malik, Adam; Barizi, Ahmad (Research and Development Institution, Darussalam Institute for Islamic Studies, 2022)
This article seeks to elucidate three significant Islamic epistemological ideas. Unquestionably, the Islamic world has been significantly impacted by the expansion of knowledge in the West. Islam has to be able to advance science for it to advance, particularly following the codification period during the Abbasid dynasty. The epistemology of Islam is impacted by the advancement of science in the West. Although the traditional Islamic intellectual riches had a unique epistemological framework, it is impossible to overlook the impact of Western epistemology on Islamic epistemology. But the traditional Islamic epistemology—that is, epistemology based on the Sufi tradition or Islamic mysticism—offers a rather strong foundation for the advancement of science in the Islamic world. Bayāni, burhāni, and ‘irfāni constitute the Islamic epistemology that is based on the heritage of Islamic mysticism.